2019
DOI: 10.1128/msphere.00663-18
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic Markers Associated with the Internalization and Processing of Aspergillus fumigatus Conidia by BEAS-2B Cells

Abstract: Conidia from the fungus Aspergillus fumigatus are notorious for their ability to stay airborne. This characteristic is believed to allow conidia to penetrate into the cleanest environments. Several hundred conidia are thought to be inhaled each day by a given individual and then expelled by mucociliary clearance. Given that airway epithelial cells make up a significant portion of the pulmonary-air interface, we set out to determine the percentage of conidia that are actually internalized after initial contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…This antifungal activity of BECs is fungistatic and occurs via a mechanism that is phosphoinositide 3-kinase dependent. The same kind of observation was made by Clark et al who found that after infecting BEAS-2B cells with A. fumigatus conidia, a large subset of conidia is rendered metabolically inactive, as measured with the metabolic marker FUN-1, while not being internalized by the cells (71).…”
Section: Molecules Potentially Active Against Aspergillus Fumigatussupporting
confidence: 66%
See 3 more Smart Citations
“…This antifungal activity of BECs is fungistatic and occurs via a mechanism that is phosphoinositide 3-kinase dependent. The same kind of observation was made by Clark et al who found that after infecting BEAS-2B cells with A. fumigatus conidia, a large subset of conidia is rendered metabolically inactive, as measured with the metabolic marker FUN-1, while not being internalized by the cells (71).…”
Section: Molecules Potentially Active Against Aspergillus Fumigatussupporting
confidence: 66%
“…Indeed, Clark et al observed the internalization of 10 to 20% of the conidia in contact with BEAS-2B cells at 6 and 9 h after challenge. In comparison, 70% of conidia in contact with macrophages were internalized after 1 h incubation (71). A 41% internalization rate has also been reported with 16HBE cells after 6 h incubation (70).…”
Section: Internalization Of Aspergillus Fumigatus Conidia By Bronchiamentioning
confidence: 51%
See 2 more Smart Citations
“…The role of the lung epithelium during Aspergillus infection has been insufficiently analyzed to date, and the published data are often contradictory. These discrepancies come from the use of epithelial cells of different origins (cell lines originating from type II ECs [e.g., A549] or bronchial epithelial adenocarcinoma, which are very different from primary ECs [204,212,213,215,216]) or the use of different mutants and morphotypes (resting conidia, swollen germinated conidia, or germ tubes) and the limited number of in vivo studies.…”
Section: Physiological Immune Response To a Fumigatus Innate Immunitymentioning
confidence: 99%